Routine histopathologic examination of the resected specimen after laparoscopic sleeve gastrectomy – what can be expected?. Issue 6 (2nd November 2021) - Taha-Mehlitz, Stephanie; Mongelli, Francesco; Sykora, Martin; Scheiwiller, Andreas; Diebold, Joachim; Metzger, Jürg; Gass, Jörn-Markus
Abstract: Background: Laparoscopic Sleeve Gastrectomy (LSG) is nowadays an established bariatric procedure. Although preoperative gastroscopy is recommended to rule out severe pathologies, there is little evidence about the role of routine histopathologic examination of resected specimens. We sought to identify the prevalence of histopathological relevant findings in patients undergoing LSG and to evaluate their impact in clinical practice. Methods: A retrospective analysis on a prospectively collected dataset on patients undergoing LSG between August 2009 and May 2018 in two bariatric centers was performed. Demographic and clinical data and histopathological results were analyzed. Results: Sixhundred-thrirteen patients were identified, mean age was 43.1 years (14–75), average body mass index was 44.8 kg/m 2 (34.4–73.9). Histopathology revealed abnormal findings in 47.97% of the patients, most common pathology was chronic non-active or minimally to moderate active gastritis ( n = 202;32.95%). Among others, Helicobacter-associated gastritis ( n = 33;5.38%), intestinal metaplasia ( n = 13;2.12%), micronodular enterochromaffine-like cell hyperplasia ( n = 2; 0.33%) and gastrointestinal stromal tumors ( n = 6; 0.98%) were present. No malignancies were found. Histopathological results required a change in the postoperative management in 48 patients (7.83%). The costs of histopathological assessment ranged between 0.77% and 2.55% of per-case payment. Conclusion: A wide range of histopathological findings occur in specimens after LSG, requiring a relevant number of patients additional therapies or surveillance. Therefore, routine histopathological examination after LSG is recommendable.